Dialog Antropologis Antaragama dengan Spiritualitas Passing Over - Stephanus Turibius Rahmat (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2017)
Inter-religious dialogue is very important discourse in the context of many religions in Indonesia. Inter-religious dialogue is the efforts to solve the difficulty of a relationship among each other followers of religions in which some conflicts and strained situations often happened. This article is a theoretical study in the purpose to describe the matter of inter-religious dialogue and formulate the model of inter-religious dialogue for creating the tolerance, the harmony, the safeness, and the peace in the religious life. By using the librarian research, the resulting study discovered that any models of inter-religious dialogue can be categorized into two models of inter-religious dialogue that are ‘theological-spiritual dialogue’ and ‘social humanity dialogue’. Theologically and spiritually, all religions have a universal message and passing over spirit (out of the border of religions) in greatly committing to the human values. Anthropologically, the presence of all religion aims to bring the enlightenment and the enthusiasm of life among their adherents. It can be concluded that anthropological dialogue based on passing over spirituality is one of the interaction model in inter-religious dialogue, or positive and constructive communication which is oriented to create the safeness and the peace in the religious life, based on passing over spirituality, in which all religions have the initial spirit of the presence that religion plays a role to illuminate (illuminative), save (prophetic), liberate (liberative) and transform (transformative). Here, religion has a self-image as rahmatan lil ‘alamīn.